(untitled) - Dormy, Emmanuel (Boca Raton, 2007)
Magnetohydrodynamics (MHD) is the study of magnetic field generation through the motion of electrically conducting fluids. The field is part of what relatively little we know about how astrophysical bodies, including planets and whole galaxies, generate magnetic fields. This collection of eight integrated articles provide a broad coverage of the central issues for the benefit of researchers and advanced students. Topics include foundations of dynamo theory, including self-excited dynamo action, nonlinearity and saturation, and dynamics of rotating fluids; natural dynamos and models, including the geodynamo, planetary dynamos, stellar dynamos, and galactic dynamos; and results of recent experiments. Appendices include materials on poloidal-toroidal coordinates and Taylor's constraint. Although contributors assume readers have a solid background in mathematics and fluid mechanics, prior knowledge of MHD, dynamo theory, geophysics and astrophysics is not required.
Keywords: Dynamo theory (Cosmic physics),Fluid dynamics,Geodynamics,Vật lý thiên văn học; Mathematical models,Mathematical models,Mathematical models